Knowledge, attitude and perception of medical students on COVID-19 vaccines: A study carried out in a Nigerian University - Orok, Edidiong; Ndem, Ekpedeme; Daniel, Eunice (Frontiers in Public Health, 2022)
Objective The purpose of this study was to assess medical students' knowledge, attitude, and perception of COVID-19 vaccines. Methods This study was a cross-sectional web-based survey conducted among undergraduate students from the faculties of Basic medical sciences and Clinical sciences, University of Uyo, Akwa Ibom State, Nigeria. The students’ knowledge was ranked as excellent (> 70%), good (50-69%) and poor (<50%). The difference in knowledge based on demographics was analysed using the Independent sample t-test. The association between demographics, and students’ perception was carried out using the Chi-square test. Analyses were conducted using SPSS software version 25. Results A total of 233 students consented to participate in the study out of which 51.1% were female. More than 20% had good knowledge while 41.2% of the participants accepted to take the COVID-19 vaccine. More than 50% of the students had positive perception of the vaccines. Conclusions There was poor knowledge and slight positive perception among majority of the students. Educational intervention in form of training of medical students should be done to improve medical students’ knowledge and perception towards COVID-19 vaccination.